2018
DOI: 10.3390/ijgi7020056
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association of Economic Development with Intercity Multimodal Transport Demand in China: A Focus on Spatial Autoregressive Analysis

Abstract: Abstract:Transportation is generally perceived as a catalyst for economic development. This has been highlighted in previous studies. However, less attention has been paid to examine the relationship between economy and transport demand by exploring spatially cross-sectional data, especially for countries with significant regional economic imbalance, like China. In this article, we assess the economic influence of intercity multimodal transport demand at the prefecture level in China. Spatial autoregressive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Different regions may respond better to different kinds of transportation, which means a region may gain better growth by developing a certain kind of transportation. In the research done by Zhao Jinbao et al, they found that in the eastern region, land transportation contributes more to the regional growth; in the central part of China, water and air transportation have a stronger correlation to GDP growth; While in the western region, land and air transportation can be more effective [9]. This study can be instructive because it can help the government to decide which kind of transportation to invest in.…”
Section: Intercity Transportation Developmentmentioning
confidence: 69%
“…Different regions may respond better to different kinds of transportation, which means a region may gain better growth by developing a certain kind of transportation. In the research done by Zhao Jinbao et al, they found that in the eastern region, land transportation contributes more to the regional growth; in the central part of China, water and air transportation have a stronger correlation to GDP growth; While in the western region, land and air transportation can be more effective [9]. This study can be instructive because it can help the government to decide which kind of transportation to invest in.…”
Section: Intercity Transportation Developmentmentioning
confidence: 69%
“…Ultimately, multimodality is expected to help creating a sustainable, integrated transport system [9]. Besides contributing to the sustainable development goals, multimodal transportation has been proven to contribute significantly to the economic development of urban territories [10][11][12].…”
Section: Related Workmentioning
confidence: 99%
“…This new fund was intended to co-finance infrastructure and environmental projects in countries with a GDP per capita of less than 90% of the EU average: Spain, Greece, Ireland and Portugal, as detailed by Holgado [31]. The role of the infrastructure is key, transportation is generally perceived as a catalyst for economic development [32].…”
Section: Evolution Of Eu Regional Policymentioning
confidence: 99%